MENINGKATKAN PASTORAL KELUARGA BAGI PASUTRI DI KUB SANTU VINSENSIUS A PAULO LINKUNGAN NIFUBOKE B PAROKI HATI YESUS YANG MAHAKUDUS NOEMUTI DALAM TERANG EFESUS 5 : 22 – 33 - Pare, Angela Rosari; Tamelab, Petrus (Pastoralia Jurnal Penelitian Dosen, 2020)
Marriage and the family is one of the most precious of human values. The Church wants to talk and provide assistance to the families and try to let your husband-wife can live up to the values of marriage. to the families who are still wavering and doubt, anxious and agitated and was looking for the truth, and to the families who unjustly blocked for mengahayati their married life freely. With the support of the first group, second group lit up, and helps other groups, then the Church offers services of service to everyone who is wondering about the ultimate purpose of marriage and the family. The pastoral care of the family is the church services maintenance reflective of God against his creation, especially against humans through pastoral service tercerminlah provide God's attitude and concern for human life. Therefore, by calling pastoral care marriage and family thing that want is shown is how the effort and the attention of the Church in the nurturing and care of the wedding so keep Harmony, sturdy, and sejathera. The planned marriage of God is cintah which is based on a marriage of love. This communion of love must always be fought so that remains so an ideal marriage, according to the draft of the God and happy. Happiness marriage can happen when Christ was present as the center of the marriage relationship (cf. Ephesians 5:22 -33). Love, loyalty and relationship between continued after built and maintained in and with Christ because Christ is the source of true life. Principal issues that occur in the KUB St. Vinsensius à Paulo Nifuboke heart of Jesus Parish Noemuti of the Holy one among others: the occurrence of the phenomenon of divorce, infidelity, prolonged bed separating this issue occurs the lack of communication interview with eight Catholic families, so the retrieved of the results of the interview. that is ethically between parents and children and the lack of family pastoral accompaniment for new couples prepare for marriage and married. To examine this issue writer implementing